Film-induced, steps for a Real Exploitation in Europe - di Cesare, Francesco; La Salandra, Anthony (Almatourism - Journal of Tourism, Culture and Territorial Development, 2015)
One of the possible ways to enhance Europe visibility, its entirety rather than a set of destinations, is implementing cooperation between the Member States especially in creating and developing trans-border thematic tourist products and experiences. One of them could be the film-induced tourism. In looking back over the past two cycles of European programming it is possible to find some examples, described in the article, in which the theme of audiovisual productions in their shooting phase in European locations has been the subject of EU attention. This article refers to some previous research results reminding how movie-induced tourism seems to be used just through sporadic attempts and therefore not developed and exploited in a strategic way. Whether from demand-side is clear what potential is inherent in the relationship between movie and tourism, on the supply side there is still much to do. As the current EC funding period (2014-2020) is favouring, at least in the first calls for proposal that came out, SMEs projects and being aware of the apparent lack of such activities developed by private businesses, the article explores new opportunities to be gathered suggesting a new exploitation path.